Serapan hara dan hasil beberapa varietas kedelai (Glycine max L. Merril) akibat ameliorasi pada tanah inceptisol Prafi - Elvira Olivia; Kati Syamsudin K. T; Purbokurniawan; Veronika L. Tuhumena (Fakultas Pertanian Universitas Papua, 2020)
This study aimed to determine the interaction of ameliorant with various soybean varieties on nutrient uptake and soybean yield on Inceptisol soil in Wasegi Indah Village, Prafi District, Manokwari Regency. This study used a separate plot design consisting of ameliorant treatment as the main plot and varieties as sub-plots. The ameliorant treatments consisted of K0 (without treatment), A15 (rice husk ash 15 tons/ha), A30 (rice husk ash 30 tons/ha), P15 (goat manure 15 tons/ha), P30 (goat manure 30 tons/ha), PA15 (goat manure 7.5 tons/ha + rice husk ash 7.5 tons/ha), and PA30 (goat manure 15 tons/ha + Rice husk ash 15 tons/ha). The 3 soybean varieties consisted of V1 (Detam-I), V2 (Demas-I), and V3 (ena-I). The results showed that there was no interaction between ameliorant and variety in all plant variables. The highest N nutrient uptake was indicated by PA30 treatment of 0.467 g and V3 variety of 0.335 g. The highest P uptake at P30 was 0.063 g and the V1 variety was 0.051 g. The highest K uptake was shown in P15 at 0.523 g and V1 at 0.424 g. The results of the application of ameliorant to several soybean varieties resulted in good production in the ameliorant treatment of 30 tons/ha (P30) goat manure at 3,210 tons/Ha and Detam-1 (V1) varieties at at 2,880 tons/Ha.